Graphite structure and method for producing same
By processing through holes on graphite plates and performing multi-metal coating, the problem of thermal conductivity of graphite structures in the prior art is solved, and efficient heat diffusion and release effects are achieved, which are suitable for a variety of electronic devices.
Patent Information
- Application Number
- CN202380052961.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to take into account both the surface direction and the thickness direction of the thermal conductivity in the graphite structure, resulting in low thermal diffusion and release efficiency.
By processing the through holes on the graphite plate, and covering the inner peripheral surface of the through holes and the whole circumference of the graphite plate with a first metal capable of forming a compound with carbon atoms, then covering the porous second metal and the third metal to form a composite structure to improve thermal conductivity.
It realizes the thermal conductivity in the thickness direction in the graphite structure, while taking into account the thermal conductivity in the surface direction, improving the thermal diffusion and release efficiency, and is suitable for semiconductor devices, vehicle-mounted devices and electronic devices.
Smart Images

Figure CN119452473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a graphite structure and a method for manufacturing the same. More specifically, the present invention relates to a graphite structure used in semiconductor devices, vehicle-mounted devices, electronic devices, etc. The graphite structure effectively diffuses and releases heat to eliminate the adverse conditions caused by the heat generation of the device, thereby maintaining and improving the function of the device. Background Art
[0002] With the popularization of high-speed communication standards in recent years, in semiconductor devices, vehicle-mounted devices, electronic equipment and other devices, due to their high output power, parts of the devices and their surroundings reach high temperatures. In order to avoid the resulting functional degradation or shutdown of the device, copper heat sinks and aluminum heat sinks have been used to conduct and release the heat to the substrate and the housing. As materials for these heat transfer and release, materials with high thermal conductivity such as metals and carbides are used.
[0003] Among them, crystalline graphite is expected to be used as a thermal diffusion material and a heat transfer material because of its high thermal conductivity. However, crystalline graphite has strong anisotropy in the plane direction and the thickness direction, so it is known that it is difficult to use crystalline graphite alone. For example, in terms of thermal conduction and strength, there are more than tens of times of difference in the plane direction and the thickness direction. In order to be used as a thermal diffusion material and a heat transfer material, it is required to be compounded with a metal with a high thermal conductivity that does not damage the thermal conduction of the crystalline graphite.
[0004] Patent document 1 discloses a graphite structure, which includes: a graphite plate having a hole; and a metal such as titanium that is easily reactive with carbon, which covers the entire circumference of the graphite plate including the inner circumference of the hole in a manner that does not block the hole. Patent document 1 states that, by using this structure, the problem of peeling between graphite layers caused by stress during heating and cooling generated in the device or electronic device to which the object is mounted can be solved.
[0005] Patent Document 2 discloses a manufacturing method of laminating graphite sheets and a binder and slicing them perpendicularly to the lamination direction to obtain a graphite structure. Since the graphite structure has the base surface of the graphite sheet arranged in the thickness direction, the thermal conductivity in the thickness direction can be improved.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 6008117
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 2009-295921 Summary of the invention
[0010] A graphite structure according to one embodiment of the present invention comprises: a graphite plate having at least one through hole extending in a direction perpendicular to a basal plane; a coating layer covering the inner peripheral surface of at least one through hole and the entire circumference of the graphite plate with a first metal capable of forming a compound with carbon atoms constituting the graphite plate; a porous second metal covering the entire circumference of the coating layer including an area surrounded by the inner peripheral surface of at least one through hole; and a third metal covering the entire circumference of the porous second metal, the graphite plate and the porous second metal being bonded to each other via the coating layer, and the third metal being bonded to the porous second metal.
[0011] A method for manufacturing a graphite structure according to one embodiment of the present invention includes: a step of machining a through hole in a graphite plate, a step of coating the inner circumference of the through hole and the entire circumference of the graphite plate with a first metal that can form a compound with carbon atoms constituting the graphite plate; a step of covering the entire circumference of a coating layer of the first metal coating the graphite plate within an area surrounded by the inner circumference of the through hole with a porous second metal; and a step of coating the entire circumference of the porous second metal with a third metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1A This is a schematic cross-sectional view showing the cross-sectional structure of the graphite structure according to the first embodiment.
[0013] Figure 1B It means from Figure 1A Schematic cross-sectional view of the cross-sectional structure of the graphite structure observed in the ZZ direction.
[0014] Figure 2 This is a flowchart of the method for producing a graphite structure according to the first embodiment.
[0015] Figure 3 Table 1 shows the production conditions of the graphite structures of Reference Examples 1 to 5 and Examples 1 to 7 and the evaluation results of the obtained graphite structures. DETAILED DESCRIPTION
[0016] In the structure of Patent Document 1, although the resistance to thermal shock can be ensured, since the thickness of the metal coating layer is 0.2 μm or less, the improvement of the thermal conductivity in the thickness direction is not achieved.
[0017] In the configuration of Patent Document 2, although the thermal conductivity in the thickness direction of the graphite sheet layer is improved, the thermal conductivity is lower than that of ordinary graphite because the binder is disposed in the direction in which the binder is laminated.
[0018] Therefore, an object of the present invention is to provide a graphite structure having high thermal conductivity in both the plane direction and the thickness direction.
[0019] The first mode of the graphite structure comprises: a graphite plate having at least one through hole penetrating in a direction orthogonal to a basal plane; a coating layer covering the inner peripheral surface of at least one through hole and the entire circumference of the graphite plate using a first metal capable of forming a compound with carbon atoms constituting the graphite plate; a porous second metal covering the entire circumference of the coating layer including an area surrounded by the inner peripheral surface of at least one through hole; and a third metal covering the entire circumference of the porous second metal, the graphite plate and the porous second metal being bonded to each other via the coating layer, and the third metal being bonded to the porous second metal.
[0020] The second embodiment of the graphite structure may be the first embodiment wherein the total area of at least one through hole is 5% to 50% of the area of the graphite plate, and the maximum area of each through hole is 5% to 50% of the area of the graphite plate.
[0021] The graphite structure of the third embodiment can be in the above-mentioned first embodiment, wherein the coating layer contains any metal selected from nickel and titanium or an alloy with these metals as the main component as the first metal, and the coating layer is formed over the inner peripheral surface of the through hole and the entire circumference of the graphite plate, and the coating layer thickness is greater than 0.01 μm and less than 20 μm.
[0022] The graphite structure of the fourth embodiment can be in the above-mentioned first embodiment, in which the porous second metal is copper or an alloy with it as the main component, formed throughout the entire circumference of the coating layer, with a thickness of not less than 0.01 mm and not more than 0.5 mm and a porosity of not less than 5% and not more than 30%.
[0023] The graphite structure of the fifth embodiment can be in the above-mentioned first embodiment, wherein the third metal is copper or an alloy with it as the main component, formed in a manner covering the outer periphery of the porous second metal, with a thickness of not less than 1 μm and not more than 100 μm, and the third metals can be joined to each other on the outside of the graphite plate.
[0024] The manufacturing method of the graphite structure of the sixth mode includes: a process of processing a through hole in a graphite plate; a process of coating the inner circumference of the through hole and the entire circumference of the graphite plate with a first metal that can form a compound with the carbon atoms constituting the graphite plate; a process of covering the entire circumference of the coating layer of the first metal coating the graphite plate within the area surrounded by the inner circumference of the through hole with a porous second metal; and a process of coating the entire circumference of the porous second metal with a third metal.
[0025] According to the graphite structure of the present invention, in the region where the through hole is provided in the graphite plate (graphite hole portion), the porous second metal becomes a heat channel, thereby being able to improve the thermal conductivity in the thickness direction. In addition, the excellent surface thermal conductivity of the graphite plate can also be taken into account in other regions of the graphite plate. In particular, since the shape processing of the graphite hole portion can also be customized in a circuit component having multiple local heat sources, the heat dissipation countermeasures of various circuit components can be improved.
[0026] Hereinafter, the graphite structure according to the embodiment of the present invention will be described with reference to the drawings. In addition, in each drawing, each element is exaggerated for the sake of ease of description.
[0027] (Implementation Method)
[0028] <Graphite structure 1>
[0029] Figure 1A This is a schematic cross-sectional view of the graphite structure 1 according to the first embodiment. Figure 1B It means from Figure 1A It should be noted that, for the sake of convenience, the base surface of the graphite plate 2 is set to be parallel to the XY plane, and the opening of the through hole 6 is set to the Z direction.
[0030] The graphite structure 1 of the first embodiment includes a graphite plate 2 having a through hole 6, a coating layer 3 covering the inner circumference of the through hole 6 and the entire circumference of the graphite plate 2 with a first metal, a porous second metal 4 covering the entire circumference of the coating layer 3, and a third metal 5 covering the entire circumference of the porous second metal 4. The first metal is a metal that can form a compound with carbon atoms constituting the graphite plate. The porous second metal 4 covers the entire circumference of the coating layer 3 including the area surrounded by the inner circumference of the through hole 6. The graphite plate 2 and the porous second metal 4 are bonded to each other via the coating layer 3. The third metal 5 is bonded to the porous second metal 4.
[0031] With the above configuration, it is possible to provide a thermally conductive member in which the graphite plate 2 is completely embedded in three types of metals (the first metal 3 , the second metal 4 , and the third metal 5 ).
[0032] <Method for producing graphite structure>
[0033] Figure 2 This is a flowchart of the method for producing a graphite structure according to the first embodiment (steps a to g).
[0034] <Graphite sheet preparation>
[0035] (1) First, as a preliminary preparation for the graphite plate 2 , arbitrary holes (graphite hole portions 6 ) are bored in advance at desired positions.
[0036] (2) Then, the entire periphery of the graphite plate 2 including the inner peripheral surface of the graphite pore portion 6 is covered with a coating layer 3 based on the first metal described later. At this time, the coating layer 3 is limited to a range that does not block the hole penetrating the graphite plate 2. The hole formed here (the inner diameter of the coating layer 3 coated on the inner peripheral surface of the graphite pore portion 6) is laid with copper powder in the subsequent manufacturing process d. copper powder setting, and forms a porous metal 4 in the manufacturing process f. sintering (thermocompression bonding).
[0037] <Manufacturing process>
[0038] a. Copper foil setting: Copper foil with a thickness of 6 μm or more and 100 μm or less is set. If the thickness is less than 6 μm, cracking and other problems may occur. On the contrary, if the thickness is greater than 100 μm, the thermal properties of the graphite structure in the plane direction may be reduced.
[0039] b. Copper powder setting: On the copper foil set in step a, copper powder or copper alloy powder with a particle size of 1 μm to 200 μm is set at a height of 10 μm to 500 μm and in a range located inside the copper foil set in step a. When the particle size is less than 1 μm, it lacks economy. On the contrary, when it is greater than 200 μm, the porosity of the graphite structure increases and the thermal characteristics are reduced. When the height is set less than 10 μm, the unnecessary porosity of the graphite structure increases and the thermal characteristics are reduced. On the contrary, when it is greater than 500 μm, the volume occupancy of copper or copper alloy in the graphite structure increases and the thermal characteristics are reduced. By extruding the copper powder when setting it, it is easy to make the thickness of the graphite structure uniform.
[0040] c. Setting of graphite plate: A graphite plate 2 prepared in advance is set on the copper powder or copper alloy powder set in step b.
[0041] d. Copper powder placement: Copper powder or copper alloy powder is placed on the graphite plate 2 placed in step c in the same manner as in step b. At this time, the graphite pores 6 are embedded with copper powder or copper alloy powder.
[0042] e. Copper foil installation: Copper foil is installed on the copper powder or copper alloy powder installed in step d in the same manner as in step a.
[0043] f. Firing (thermocompression bonding): Apply 0.05kgf / cm2 of inert atmosphere at 1100°C to 1200°C to the finished product of step e. 2 Above and 1kgf / cm 2The following pressure is applied for hot pressing. When the temperature is less than 1100°C, the copper powder or copper alloy powder may not be able to be joined. On the contrary, when the temperature is greater than 1200°C, not only the copper powder or copper alloy powder is completely melted and it is difficult to maintain the posture of the graphite plate 2, but also the surface copper foil may be thermally decomposed. In addition, when the pressure is less than 0.05kgf / cm 2 In the case of 1kgf / cm, the bonding of copper powder or copper alloy powder may not be promoted. 2 Thus, the second porous metal 4 is formed by the bonding of copper powder or copper alloy powder.
[0044] g. Peripheral bonding: The upper and lower copper foils existing on the outside relative to step b and step d are bonded. The bonding method is not particularly limited and can be selected from laser welding, thermal bonding, ultrasonic bonding, solder bonding, etc. In this way, the copper foils are bonded to form the surface metal (third metal) 5.
[0045] Through the above steps a to g, the graphite structure 1 is manufactured in which the graphite plate 2 and the porous metal 4 are bonded to each other via the coating layer 3 , and the surface metal 5 and the porous metal 4 are bonded to each other.
[0046] <Graphite plate 2>
[0047] The graphite plate 2 is a crystalline graphite having a size of 50 mm × 50 mm and a thickness of 0.2 mm. The graphite plate 2 is made by heating a polyimide film to above 2500°C in an inert gas atmosphere. It is desired that the thermal conductivity of the graphite plate 2 in the surface direction is above 1200 W / m·K, preferably above 1300 W / m·K. In addition, in order to form the coating layer 3 and the porous metal 4 in the subsequent process, a through hole (graphite hole portion 6) of Φ4 mm is formed in the graphite plate 2 by press working. The opening rate of the through hole relative to the area of the graphite plate 2 is preferably in the range of above 5% and below 50%. The size, shape, and number of the through hole can be arbitrarily set within the range of the specifications of the final graphite structure 1. When the opening rate is less than 5%, there is a case where the copper powder or copper alloy powder is completely melted and it is difficult to maintain the posture of the graphite plate 2. On the contrary, when the opening rate is greater than 50%, there is a case where the thermal properties of the graphite structure 1 are reduced. The graphite plate 2 may have a plurality of through holes 6. The plurality of through holes 6 may have different areas. The maximum area of each through hole is preferably 5% or more and 50% or less of the area of the graphite plate. The maximum area of each through hole refers to the largest area among the plurality of different areas.
[0048] <Clad layer (first metal) 3>
[0049] The coating layer 3 contains any metal of nickel and titanium or an alloy with the metal as the main component as the first metal. The coating layer 3 is formed over the inner circumference of the through hole 6 and the entire circumference of the graphite plate 2. The thickness of the coating layer 3 is greater than 0.01 μm and less than 20 μm. The method for forming the coating layer 3 can be selected from plating, evaporation, sputtering, etc. In the case where the thickness is less than 0.01 μm, problems such as voids may occur. On the contrary, in the case where the thickness is greater than 20 μm, due to the low thermal conductivity of nickel and titanium, there is a case where the thermal characteristics as a graphite structure are reduced. In addition, when the thickness is extremely increased, it is difficult to achieve miniaturization of devices and electronic equipment.
[0050] <Porous Metal (Second Metal) 4>
[0051] The porous metal (second metal) 4 is a sintered body formed by hot pressing of copper powder or copper alloy powder. The porous metal 4 is formed all around the coating layer 3. The thickness of the porous metal 4 is greater than 10 μm and less than 500 μm. The porosity indicating porosity is greater than 5% and less than 30%. When the thickness is less than 10 μm, the particle size of the copper powder in step b and step d is restricted, and extrusion becomes difficult. On the contrary, when the thickness is greater than 500 μm, the thermal properties of the graphite structure are reduced. When the porosity is less than 5%, the copper powder or copper alloy powder is completely melted and it is difficult to maintain the posture of the graphite plate 2. On the contrary, when the porosity is greater than 30%, the thermal properties of the graphite structure 1 are reduced.
[0052] It should be noted that, here, the porous metal (second metal) is a sintered body formed by thermocompression bonding of copper powder or copper alloy powder, but the present invention is not limited thereto and may be other porous metals.
[0053] <Surface metal (third metal) 5>
[0054] The surface metal (third metal) 5 can be selected from copper foils with a thickness of 6 μm or more and 100 μm or less. When the thickness is less than 6 μm, cracking and other problems may occur. On the contrary, when the thickness is greater than 100 μm, the copper foil is difficult to bend, and peripheral bonding may become difficult.
[0055] It should be noted that, although the case where copper foil is bonded as the surface metal (third metal) is described here, the present invention is not limited to this and other metals may be used as long as the surface is covered.
[0056] (Examples 1 to 7 and Reference Examples 1 to 5)
[0057] A graphite structure 1 is produced using a graphite plate 2 produced based on the present embodiment. As a common standard, the graphite plate 2 has a size of 50 mm × 50 mm × 0.2 mmt. The coating layer 3 is formed by nickel plating and has a thickness of 10 μm. The porous metal 4 is formed of copper powder having a particle size of less than 180 μm. The surface metal 5 has a size of 70 mm × 70 mm × 0.01 mmt. Other standards are described in the following embodiments. The heating and cooling rate during hot pressing is 10°C / min. In order to stabilize the temperature at the set maximum temperature, the temperature is maintained for 30 minutes or 60 minutes at 0.1 kgf / cm 2 The process is carried out under pressurized pressure.
[0058] The porosity is calculated based on cross-sectional observation of the produced graphite structure 1. The thermal conductivity in the thickness direction is measured using TIMTester (manufactured by ANALYSISTECH). As for the thermal conductivity in the plane direction, since there is no measurement method for a composite body like the graphite structure 1 of the present invention, it is calculated based on the mixing rule. A graphite structure having a thermal conductivity of 50 W / m·K or more in the thickness direction and a thermal conductivity of 600 W / m·K or more in the plane direction is judged to be qualified. Figure 3 Table 1 shows the production conditions of the graphite structures of Reference Examples 1 to 5 and Examples 1 to 7 and the evaluation results of the obtained graphite structures.
[0059] (Reference Example 1)
[0060] The opening ratio of the graphite plate was set to 15% of the total area of the graphite plate, and the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 50%. The thermal compression bonding was performed under the conditions of setting the maximum temperature to 950°C and the temperature holding time to 30 minutes. The evaluation results showed that the porosity of the porous metal was more than 80%, and the thermal conductivity was also unqualified.
[0061] (Reference Example 2)
[0062] The member conditions were the same as those in Reference Example 1, and thermocompression bonding was performed at a maximum temperature of 1050° C. and a temperature holding time of 30 minutes. As a result, the porosity of the porous metal was about 40%, and the thermal conductivity was also unacceptable.
[0063] (Example 1)
[0064] The member conditions were the same as those in Reference Example 1, and the thermocompression bonding was performed at a maximum temperature of 1100° C. and a temperature holding time of 60 minutes. The evaluation results showed that the porosity of the porous metal was about 20% and the thermal conductivity was acceptable.
[0065] (Example 2)
[0066] The member conditions were the same as those in Reference Example 1, and the thermocompression bonding was performed at a maximum temperature of 1150° C. and a temperature holding time of 30 minutes. The evaluation results showed that the porosity of the porous metal was about 25% and the thermal conductivity was acceptable.
[0067] (Example 3)
[0068] The member conditions were the same as those in Reference Example 1, and the thermocompression bonding was performed at a maximum temperature of 1200° C. and a temperature holding time of 30 minutes. The evaluation results showed that the porosity of the porous metal was about 5% and the thermal conductivity was acceptable.
[0069] (Reference Example 3)
[0070] The member conditions were the same as those in Reference Example 1, and thermocompression bonding was performed at a maximum temperature of 1300° C. and a temperature holding time of 30 minutes. The evaluation results showed that the copper was completely melted and eluted out of the system, so it was deemed unacceptable.
[0071] (Reference Example 4)
[0072] The opening ratio of the graphite plate was set to 50% of the total area of the graphite plate, and the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 50%. The hot pressing was performed under the conditions of setting the maximum temperature to 1100°C and the temperature holding time to 60 minutes. The evaluation results showed that the porosity of the porous metal was about 20%, and only the thermal conductivity in the surface direction was unqualified. The reason is that the increase in the opening ratio of the graphite reduces the heat transfer capacity in the surface direction.
[0073] (Example 4)
[0074] The opening ratio of the graphite plate was set to 50% of the total area of the graphite plate, the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 33%, and the thermal compression bonding conditions were the same as those in Reference Example 4. The evaluation results showed that the porosity of the porous metal was about 20%, and the thermal conductivity was acceptable.
[0075] (Example 5)
[0076] The opening ratio of the graphite plate was set to 5% of the total area of the graphite plate, the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 50%, and the thermal compression bonding conditions were the same as those in Reference Example 4. The evaluation results showed that the porosity of the porous metal was about 20%, and the thermal conductivity was acceptable.
[0077] (Example 6)
[0078] The opening ratio of the graphite plate was set to 50% of the total area of the graphite plate, the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 87%, and the thermal compression bonding conditions were the same as those in Reference Example 4. The evaluation results showed that the porosity of the porous metal was about 20%, and the thermal conductivity was acceptable.
[0079] (Reference Example 5)
[0080] The opening ratio of the graphite plate was set to 50% of the total area of the graphite plate, the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 28%, and the thermal compression bonding conditions were the same as those in Reference Example 4. The evaluation results showed that the porosity of the porous metal was about 20%, and only the thermal conductivity in the surface direction was unqualified. The reason is that the proportion of the graphite plate was reduced, thereby reducing the heat transfer capacity in the surface direction.
[0081] (Example 7)
[0082] The opening ratio of the graphite plate was set to 5% of the total area of the graphite plate, the ratio of the graphite plate thickness to the total thickness of the graphite structure was set to 28%, and the thermal compression bonding conditions were the same as those in Reference Example 4. The evaluation results showed that the porosity of the porous metal was about 20%, and the thermal conductivity was acceptable.
[0083] <Effect>
[0084] The structure of this embodiment can provide a graphite structure that increases the thermal conductivity in the thickness direction to the same level as metal and makes the thermal conductivity in the surface direction more than 1.5 times that of pure copper. In addition, since solid-phase bonding can be performed, the positioning of the built-in graphite is easy, and it can also cope with point-like heat sources.
[0085] Industrial Applicability
[0086] The graphite structure of the present invention has excellent thermal conductivity in both the surface direction and the thickness direction and can therefore be applied to fields such as semiconductor devices, vehicle-mounted devices, and electronic devices having a local heat source, and is therefore industrially useful.
[0087] Description of Reference Numerals
[0088] 1 Graphite structure, 2 Graphite plate, 3 Covering layer, 4 Porous second metal, 5 Third metal, 6 Graphite pores.
Claims
1. A graphite structure, comprising: A graphite plate having at least one through hole penetrating in a direction perpendicular to the base surface; a coating layer covering the inner peripheral surface of the at least one through hole and the entire circumference of the graphite plate using a first metal capable of forming a compound with carbon atoms constituting the graphite plate; a porous second metal covering the entire circumference of the coating layer including a region surrounded by the inner circumferential surface of the at least one through-hole; and a third metal covering the entire circumference of the porous second metal, in, The graphite plate and the porous second metal are bonded to each other via the coating layer, and the third metal is bonded to the porous second metal.
2. The graphite structure according to claim 1, wherein The total area of the at least one through hole is 5% to 50% of the area of the graphite plate, and the maximum area of each through hole is 5% to 50% of the area of the graphite plate.
3. The graphite structure according to claim 1, wherein The coating layer includes any metal of nickel and titanium or an alloy mainly composed of the metals as the first metal, and the coating layer is formed over the inner peripheral surface of the through hole and the entire circumference of the graphite plate. The thickness of the coating layer is greater than or equal to 0.01 μm and less than or equal to 20 μm.
4. The graphite structure according to claim 1, wherein The porous second metal is copper or an alloy containing it as a main component, is formed over the entire circumference of the coating layer, has a thickness of 0.01 mm to 0.5 mm, and has a porosity of 5% to 30%.
5. The graphite structure according to claim 1, wherein The third metal is copper or an alloy containing copper as a main component, is formed so as to cover the outer periphery of the porous second metal, and has a thickness of 1 μm to 100 μm. The third metals are bonded to each other on the outer sides of the graphite plates.
6. A method for manufacturing a graphite structure, the method comprising: Process of machining through holes in graphite plates; A step of coating the inner peripheral surface of the through hole and the entire periphery of the graphite plate with a first metal capable of forming a compound with carbon atoms constituting the graphite plate; The method comprises the steps of covering the entire circumference of the coating layer of the first metal covering the graphite plate with a porous second metal within the area surrounded by the inner circumferential surface of the through hole; and A step of coating the entire circumference of the porous second metal with a third metal.
Citation Information
Patent Citations
Driving device of starter of vehicle with automatic transmission
JP1985008117A
Heat-conducting sheet where graphite is oriented in thickness direction
JP2009295921A